DEVELOPMENT WOMEN- FRIENDLY FINANCIAL SERVICES: A CASE STUDY OF LIVESTOCK BREEDERS’ COOPERATIVE SOCIETIES IN VAVUNIYA - Mangaleswaran, T.; Morais, N.; Jeyaseelan, G. (University of Jaffna, 2010)
Access to affordable financial services is vital to economically empower women and men in the dairy sector I rural areas. In Sri Lanka there have been few studies in investigating the impacts of financial services for women. Rural women largely depend on the informal sector to fulfill their diverse financial needs. Access to commercial financial services for women and men is essential in the pot- conflict situation, which can accelerate the process of livelihood recovery. The objective of the study is to explore and map women- friendly financial services to the Livestock Breeders Cooperative Societies (LBCS) in Vavuniya. The study adopted a qualitative methodology to explore the questions. The study primarily used Focus Group Discussions (FGD), individual interviews and case studies. The data sources include LBCS executive committees and women members. (ii) Assistant Commissioner of Cooperative Societies in Mannar an Jaffna and (iv) Women Rural development societies (WRDS). The study finds that lack of access to financial services to women members of dairy cooperatives remains a major constraint for their economic advancement. It also identifies factors such as women’s poor financial planning in credit, saving and insurance services, less linkage with formal financial institutions, lack of knowledge and confidence in banking transactions inability to invest time and provide needed documents and securities to the formal bank, that hamper access to formal financial services. It recommends that financial institutions relax physical collateral requirements and seek alternatives such as bulk loans to the cooperatives based on their capacity to generate income. It also recommends that the cooperatives and the department of cooperatives to take steps to train women members in financial literacy, facilitate and support linkages among the various types of rural finance providers and promote learning and capacity- building networks of practitioners. The cooperative department can develop specific provision in it rules and regulations and support systems towards women owned cooperatives. Thu it can play a vital role in women economic friendly policies within the financial institutions and cooperative system.
Keywords: Financial Services; Women; Livestock n Cooperatives